Outsourcing versus in-house staff : a case of the University of Limpopo's support staff - Ramakadi, Lesiba Phillip (University of Limpopo, 2017)
The research is focused on outsourcing versus in-house staff in the case of the University of Limpopo. Since the outsourcing path was adopted in 2002, no formal study was instituted by UL to ascertain whether the decision had positive effects on the university’s financial status and former employees’ welfare. One of the impediments that posed a real threat to the UL’s outsourcing agenda was the lack of a guiding document to adequately direct the negotiation process. Lack of feedback and lack of a vibrant communication plan as the main variables that triggered a climate of mistrust between the PCS and stakeholders were identified. This study seeks to determine which option, namely outsourcing versus in-house staff complement will be the most advantageous to UL. The idea taken by the UL in 2002 to outsource what was perceived as non-core operations was an idea that was never easy to implement and ultimately failed to achieve its originally intended purpose. This study opted for the qualitative method because it relied on the views of UL’s former employees who were directly affected by the university’s 2002 outsourcing arrangement. The population of this study consisted of one hundred and fifty (150) people comprising of UL’s in-house employees in the UL. The process of selecting the participants was based on the purposive sampling method. The sample size for this study was 38 of the outsourced operational support staff From the results obtained from the study, a conclusion was drawn that the outsourcing arrangement did not provide any significant benefit to any of the affected parties. The recommendations on measures to improve the effectiveness of UL’s outsourcing arrangement were made and described in detail in chapter five of this study. Recommendations for further studies were also made in chapter five as being inevitable because there is no research that is complete in itself
Thesis (MBA.) -- University of Limpopo, 2017
Keywords: Outsourcing; Inhouse staff; University of Limpopo; Contracting out; In-house services (Business).